Poloniści wobec charakterystyki postaci. Rekonesans badawczy - Grzegórzek, Mirosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article presents the outcome of a pilot survey carried out among Polish teachers of different educational stages, considering a figure’s characteristics as a school form of statement. Through both the quantitative and qualitative analysis of the gathered empirical material the author tries to define the place of a figure’s characteristics of scholastic activities, searching for the answer to such questions as: how do teachers perceive the usefulness of the relevant genre outside the sphere of the school communication? What methods do they use in their work with this form of statement in connection with its determined didactic aims? In which direction should the possible changes in approach to characterising at school go? It is all for the sake of the work during the lessons with the use of the genre, so it would serve the development of the young people’ subjectivity and respond to the challenges of modern interpersonal relations.
Keywords: school genres; figure’s characteristics; methods; didactic aims; interpersonal relations